2021
DOI: 10.1302/2633-1462.27.bjo-2021-0049.r1
|View full text |Cite
|
Sign up to set email alerts
|

Acute plate fixation of displaced midshaft clavicular fractures is not associated with earlier return of normal shoulder function when union is achieved

Abstract: Aims It is unclear whether acute plate fixation facilitates earlier return of normal shoulder function following a displaced mid-shaft clavicular fracture compared with nonoperative management when union occurs. The primary aim of this study was to establish whether acute plate fixation was associated with a greater return of normal shoulder function when compared with nonoperative management in patients who unite their fractures. The secondary aim was to investigate whether there were identifiable predictors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Robinson et al 35 conducted a prospective multicentre RCT and observed that fixation was associated with better functional outcomes. Nicholson et al 12 concluded that acute plate fixation of displaced MSCFs was not associated with earlier return of normal shoulder function when union was achieved. Systematic reviews and meta-analyses.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Robinson et al 35 conducted a prospective multicentre RCT and observed that fixation was associated with better functional outcomes. Nicholson et al 12 concluded that acute plate fixation of displaced MSCFs was not associated with earlier return of normal shoulder function when union was achieved. Systematic reviews and meta-analyses.…”
Section: Resultsmentioning
confidence: 99%
“…An increasing body of evidence subsequently published has suggested that equivalent outcomes can be achieved with nonoperative management. 12 , 14 , 16 , 19 , 34 Additionally Nicholson et al 38 concluded that routine plate fixation of displaced MSCFs was not cost-effective. They suggested that a targeted approach to fixation of patients who are at higher risk of nonunion would be more efficient.…”
Section: Discussionmentioning
confidence: 99%